Proactive behaviour as a mediator in the relationship between quality of work life career - Ling, Nyuk Ping; Nur Fatihah, Abdullah Bandar; Farida, Abdul Halim; Agatha Lamentan, Muda (Universiti Malaysia Sarawak (UNIMAS), 2017)
Achieving career success among employees is a primary concern for both individuals and organisations. Career success acts as a powerful motivator for one to advance great progress, such as improving his or her job performance and achieving more success. Quality of work life is in accordance with various needs of individuals’ well-beings in the workplace, which may promote career success. Additionally, instead of having knowledge and skills required, individuals should possess positive personalities and right attitude to ensure that they always exert their best endeavours to achieve career success. This study examined the mediating effect of proactive behavior on the relationship between quality of work life and career success. Self-administered surveys were employed for data collection among 304 married academicians from two selected Public Institutions of Higher Learning. Data were analysed by using Analysis Moment of Structures Software (AMOS) for Structural Equation Modelling (SEM). Results indicated that a partial mediation effect of proactive behaviour was established on the relationship between quality of work life and career success. It can be concluded that the quality of work life can positively influence career success among academicians. If they, however, also have proactive behaviour, they will be eagerly urged to achieve higher levels of career success.